2007
DOI: 10.1007/s00595-006-3402-7
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of an Aorto-Ileal-Conduit Fistula with an Endovascular Stent Graft: Report of a Case

Abstract: A 55-year-old man presented with a massive hemorrhage from the ileal conduit of the left ureter. He had previously undergone a total pelvic exenteration with ileal conduit construction of the ureters due to rectal carcinoma. A right ureteroarterial fi stula developed, and he underwent an excision of the right common iliac artery with a femorofemoral bypass and a right cutaneous ureterostomy. Seven months later, a pseudoaneurysm developed at the aortic stump, followed by an aorto-ileal-conduit fi stula. The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Moreover, a fistula between the iliac artery and the ileal conduit is even unusual, with only a few reported cases. 2,3…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a fistula between the iliac artery and the ileal conduit is even unusual, with only a few reported cases. 2,3…”
Section: Discussionmentioning
confidence: 99%
“…5 Less commonly reported are cases of fistulas between urinary conduits and arteries. [6][7][8][9][10] In a review of 80 cases of ureterovascular fistulas, Bergqvist and colleagues reported that 36% occurred in the setting of ileal conduits, suggesting even when a urinary diversion is present, a fistula to the ureter is more likely. 11 Certainly, the least reported type of fistula is one between a neobladder and artery.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Stent grafting for mycotic aortic aneurysm has been reported in several articles. [6][7][8][9][10][11][12] We report a case of stent grafting as bridge treatment before a radical operation. Although the infection recurred 7 months after stent grafting, we performed graft replacement successfully using rifampicin-soaked gelatin sealed polyester graft and omentopexy, as in situ treatment.…”
Section: Introductionmentioning
confidence: 98%